Health Safety and Hajj Preparedness (K3Haji) - M . Sukaelan, M. Sukaelan; Marhumah, Marhumah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Hajj is a worship that is obligatory once in a lifetime which is highly anticipated by all Muslims in the world, including Indonesia, all of them go to one place, namely Mecca, resulting in a very large mass buildup, so it is necessary to anticipate safety, health and preparedness from the moment of departure. , the implementation of the ritual worship until the time of staying and staying overnight at the place. Data on the implementation were taken from the website, observations, experiences during the pilgrimage and observations and experiences while serving as a speaker on hajj safety, health and preparedness at KBIH (Hajj guidance group) Multazam Yogyakarta City from 2017-2023. Where data is obtained that most of the prospective pilgrims do not know the situation and condition of the place of worship, while on the way, during worship and during activities at the hotel and how to behave when an emergency occurs (fire, heart attack, both yourself and other pilgrims) ) mainly related to hazards, risks and how to deal with them properly and correctly.